Agricultural Marketing Extension services in a changing, scenario - Vikram Singh,; J.P.Singh, (Journal of Agricultural Extension Management, 2025)
India has now entered a new era of globalization and economic liberalization. The possibilities of increased trade in the global markets demand that the country becomes efficient, competitive and innovative both in production and marketing. Opportunities thrown open by the globalization process should be fully exploited by concerted action by all those engaged in the production, marketing and trade in agricultural commodities. Agricultural marketing has been receiving a lower priority than production. There is a tendency to be preoccupied with increasing production without a matching concern to improve and strengthen marketing. The government's investment in agricultural marketing has been an insignificant proportion of the total investment in agriculture and allied sectors at the centre and state levels. Rapid urbanization, globalization and liberalization, leading to greater competitiveness and the problem of adjusting agriculture with the economy and increasing specialization of production in agriculture and government intervention have added new dimensions to agricultural marketing